MARRIAGE CONTRACT - IS A GUARANTEE OF FAMILY STRENGTH - U. Abdurasulov (Scholars Digest Publishing, 2023)
In this article, it is explained in detail that the family is a sacred place and the rules of marriage are defined by the existing normative documents. We can say that a healthy environment in the immediate family, a healthy ideology, and a mentally healthy person are the source of support. It was thought that the family, which is the strong support of our society, not only educates the people of tomorrow, but also needs to be able to form the ability to care for the motherland and tomorrow. Currently, Article 17 on "Medical examination of married people" has been introduced into the Family Code as a new norm. In this article, it is established that people getting married will undergo a free medical examination in the institutions of the state health care system. A marriage contract can be concluded before the marriage is registered in the state register or during the marriage. The contract concluded before the state registration of the marriage takes effect from the date of its state registration. The contract is made in writing and must be confirmed by a notary.
Keywords: Family Code, marriage, medical examination, marriage contract, power of attorney, divorce.